Bortezomib induces cellular senescence in A549 lung cancer cells by stimulating telomere shortening. (22nd August 2022) - Wang, Lei; Yin, Hang; Huang, Shiren; Huang, Sini; Huang, Congcong; Zhang, Zhao; Liu, Hui
Bortezomib (BTZ) is a first-generation proteasome inhibitor with anti-tumor properties for multiple myeloma and mantle cell lymphoma. Increasing evidence has shown that BTZ exhibits toxic effects on diverse tumor cells, including non-small cell lung cancer (NSCLC) cells. However, the mechanism has not been fully evaluated. Here, we examined the regulatory effect of BTZ on cellular senescence, a potent tumor suppressive mechanism, in NSCLC cell lines. SA-β-gal staining assay showed that BTZ caused a significant increase in β-Gal positive A549 cells. BTZ also induced cell cycle arrest on G0/G1 phase in A549 cells. Furthermore, telomerase activity was markedly reduced in A549 cells treated with BTZ. BTZ reduced the expression levels of hTERT, and the key proteins binding to telomeric DNA, including POT1 and TIN2. It also induced the expressions of the cell cycle-associated tumor suppressors p53 and p21 in A549 cells. Moreover, hTERT overexpression abolished the effects of BTZ on A549 cells. These results show that BTZ induced cellular senescence by stimulating telomere shortening. Our results provide experimental data for the potential clinical application of BTZ in NSCLC treatment.